Comparing Citizens' Trust in the Police Across European Countries: An Assessment of Cross-Country Measurement Equivalence. (March 2014) - Schaap, Dorian; Scheepers, Peer
International comparative studies on citizens' trust in the police have become more common. However, they generally tend to ignore the fundamental question of whether comparisons between countries are actually valid. We address this knowledge gap by conducting measurement equivalence tests on trust in the police within the framework of legal and political trust, arguing that a deviant position of trust in the police within this framework in a certain country indicates comparability issues. We analyze data from the European Social Survey in 26 European nations, finding that both trust in the police and trust in other institutions are empirically comparable within most, but not all, of Europe. We also note substantial variation across countries in levels of trust, especially in terms of differences between Eastern Europe and Western Europe. We conclude that future cross-national comparisons of citizens' trust in institutions, and especially the police, should systematically account for equivalence issues to prevent invalid conclusions and should exercise constraint in including culturally very diverse countries.